Healthcare Utilization and Costs of Systemic Lupus Erythematosus in Medicaid. (4th December 2012) - Kan, Hong J.; Song, Xue; Johnson, Barbara H.; Bechtel, Benno; O'Sullivan, Donna; Molta, Charles T.
Abstract : Objective . Healthcare utilization and costs associated with systemic lupus erythematosus (SLE) in a US Medicaid population were examined. Methods . Patients ≥ 18 years old with SLE diagnosis (ICD-9-CM 710.0x) were extracted from a large Medicaid database 2002–2009. Index date was date of the first SLE diagnosis. Patients with and without SLE were matched. All patients had a variable length of followup with a minimum of 12 months. Annualized healthcare utilization and costs associated with SLE and costs of SLE flares were assessed during the followup period. Multivariate regressions were conducted to estimate incremental healthcare utilization and costs associated with SLE. Results . A total of 14, 777 SLE patients met the study criteria, and 14, 262 were matched to non-SLE patients. SLE patients had significantly higher healthcare utilization per year than their matched controls. The estimated incremental annual cost associated with SLE was $10, 984, with the highest increase in inpatient costs (P < 0.001 ). Cost per flare was $11, 716 for severe flares, $562 for moderate flares, and $129 for mild flares. Annual total costs for patients with severe flares were $49, 754. Conclusions . SLE patients had significantly higher healthcare resource utilization and costs than non-SLE patients. Patients with severe flares had the highest costs.